Comparative Study on Drying Characteristics and Quality of Apple Cubes Dried in Two Different Microwave Dryers - Yuhe Ma; Xiaoju Tian; Yingqiang Wang; Hongxia Zhao; Jialing Song (Polish Journal of Food and Nutrition Sciences)
A rotary plate microwave dryer (RMD) and a newly-developed microwave convection coupled dryer (MCD) were used to dry apple cubes. The effects of microwave output power on drying, heating characteristics and quality attributes including scorching rate, color parameters, rehydration ratio, shrinkage, hardness, and sensory scores of the apple cubes were investigated and compared. The results showed that the microwave power required to complete drying in RMD was only 1/6 of that in MCD at the same microwave power density. Total drying time was 120, 60 and 30 min at 70, 210 and 350 W in RMD, respectively, while 160, 90, 80 and 60 min at 400; 800; 1,200; and 1,600 W in MCD, respectively. Compared with the products dried using hot air, the apple cubes dried in both dryers at the low microwave power had better rehydration capacity, less shrinkage and lower hardness as well as a* and b * value of color. Application of microwave power of over 800 W in MCD and over 210 W in RMD caused the increase in scorching rate as well as decreased the L * value and the sensory quality of the apple cubes. Microwave drying in MCD with temperature control improved the quality of the dried product. The microwave drying conditions suitable for the apple cubes were 400 W in MCD and 1,600 W in MCD with temperature control followed by 70 W in RMD; the products obtained under these three condition variants had superior or comparable quality to the products obtained upon conventional hot air-drying.